Quality improvement of plant-based white chocolate enriched with encapsulated blueberry juice - Rossi Indiarto; Natallina Wiranto Putri; Fetriyuna Fetriyuna; Edy Subroto; Arif Nanda Irawan; Dimas Rahadian Aji Muhammad; Mohd Nizam Lani (Food Chemistry Advances)
White chocolate contains no cocoa solids, resulting in low antioxidant activity and limited suitability for vegans and lactose-intolerant individuals due to its dairy content. This study investigated the reformulation of white chocolate using almond milk (AM), soy protein isolate (SPI), and encapsulated blueberry juice (EBJ) in varying ratios to enhance its physicochemical, antioxidant, and sensory properties. The quality attributes evaluated included color, texture, polymorphism, particle size distribution, melting point, microstructure, protein content, fat content, phenolic content, flavonoid content, antioxidant activity, and sensory characteristics. The results indicated that substituting SPI and AM significantly affected the physicochemical and sensory characteristics, except for springiness, cohesiveness, and aroma. However, higher levels of SPI decreased product acceptability. Incorporating 10 % (w/w) EBJ into vegan white chocolate (VWC) significantly increased phenolic content from 11.75 to 18.57 mg GAE/100 g, total flavonoids from 3.88 to 11.03 mg QE/100 g, and DPPH IC₅₀ from 48.22 to 31.78 mg/ml. VWC exhibited desirable V(β) and VI(β) crystal forms, with median particle sizes (78.37–104.8 µm) comparable to those of commercial products. VWC was accepted by the panelists, with VWC1-EBJ (AM 25 % and EBJ 10 %) showing the best results across all tested parameters. Therefore, this research presents a promising chocolate formula that is both appealing and healthy, particularly for consumers seeking lactose-free and vegan products.